2009
DOI: 10.3171/2007.12.17287
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for observing cerebral cisterns and ventricles via a percutaneous lumbosacral route by using fine, flexible fiberscopes

Abstract: The approach to the supraspinal structures via the lumbosacral route by using a fine, flexible fiberscope may provide a new, minimally invasive, and safe way to observe the cerebral cisterns and/or brainstem regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…7,28 Shimoji et al 26 reported that they successfully advanced a fiberscope to the fourth and third ventricles via a percutaneous route. Karakhan et al 14 described different approaches, including a dorsal paramedian approach to the intradural space via interlaminar fenestration or hemilaminectomy.…”
Section: Discussionmentioning
confidence: 99%
“…7,28 Shimoji et al 26 reported that they successfully advanced a fiberscope to the fourth and third ventricles via a percutaneous route. Karakhan et al 14 described different approaches, including a dorsal paramedian approach to the intradural space via interlaminar fenestration or hemilaminectomy.…”
Section: Discussionmentioning
confidence: 99%
“…A subarachno-epidurostomy creates a pressure gradient that keeps the stoma open (as in the case of a third ventriculocisternostomy) and leads to a long-term improvement in CSF fl ow. It is interesting that recently fi beroscopy via the lumbosacral route has been suggested as a novel approach to observe cerebral ventricles and cisterns; in a series of 31 patients, chronic arachnoiditis necessitated interruption of the procedure in 6 patients [23] .…”
Section: Thecaloscopy Techniquementioning
confidence: 99%
“…Diagnosis and/or treatment of tethered cord syndrome, arachnoiditis, and spinal subdural hematoma can be established. [23][24][25][26] A novel endoscopic technique for the visualization and surgical manipulation of the filum terminale with no assistance from a loupe or microscope was described and supported with Key words -Filum terminale -Interlaminar -Minimal invasive spine surgery -Spinal endoscopy -Tethered cord syndrome -Untethering histopathologic examination. The utility, safety, and feasibility of this method were investigated in fresh postmortem adult human cadavers.…”
Section: Introductionmentioning
confidence: 99%